High-elasticity high-viscosity asphalt as well as preparation method and application thereof
By adding vinyl, thiol, silver ions and nanotitanium dioxide to SBS modified asphalt, a cross-linking network and silver-carrying nanotitanium dioxide are formed, the problem of large amount of SBS and asphalt flue gas is solved, and high elasticity and low flue gas asphalt is achieved Materials, reduce costs and improve the performance of asphalt.
Patent Information
- Application Number
- CN202411495568.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The amount of SBS added to existing SBS modified asphalt is too large, which leads to high costs and is difficult to effectively reduce the generation of reflective cracks. At the same time, harmful asphalt flue gas is easily generated during asphalt laying.
Modified SBS, including vinyl and sulfhydryl groups, catalyzed by photoinitiator, form a crosslinking network structure, partially replace SBS, and add silver ions and nanotitanium dioxide to the modified SBS to form silver-carrying nanotitanium dioxide to improve the elasticity of asphalt and smoke removal effect.
It effectively reduces the amount of SBS added, improves the elasticity and viscosity of asphalt, and significantly reduces the generation of asphalt flue gas, improves the crack resistance and flue gas treatment effect of asphalt.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer modified asphalt, and more specifically, to a high-elasticity and high-viscosity asphalt and a preparation method and application thereof. Background Art
[0002] With the development and improvement of China's highway network, many highways have entered the maintenance and renovation stage. Whether it is the maintenance of old roads or the renovation and upgrading of low-grade roads, laying a new asphalt surface layer on the original road surface is one of the more common measures at present. However, if ordinary asphalt materials are laid directly, the horizontal cracks, longitudinal cracks, cracks, plate corner cracks and structural joints of the original old road surface will quickly reflect to the asphalt overlay surface layer, forming reflective cracks, which will cause more serious damage.
[0003] Polymer modified asphalt is obtained by adding polymers to road asphalt to obtain excellent performance. For example, SBS modified asphalt has extremely excellent low-temperature crack resistance, fatigue resistance and excellent elastic recovery performance, which can effectively reduce the occurrence of reflective cracks when paved on the original road surface. However, the amount of SBS added to SBS modified asphalt is too large and the cost is too high, so it still needs to be improved. Summary of the invention
[0004] In order to overcome the defect of excessive addition of SBS in conventional SBS modified asphalt, the present application provides a high-elasticity and high-viscosity asphalt with a smaller addition amount of SBS, and a preparation method and application thereof.
[0005] In the first aspect, the present application provides a high-elasticity and high-viscosity asphalt, which adopts the following technical solution: A high-elastic and high-viscosity asphalt comprises the following raw materials in parts by weight: 90-110 parts of base asphalt, 12-18 parts of modified SBS and 1-2 parts of photoinitiator, wherein the modified SBS contains vinyl and mercapto groups, and the modified SBS is loaded with silver ions and titanium dioxide.
[0006] Since the modified SBS contains a large amount of vinyl and thiol groups at the same time, under the catalysis of the photoinitiator, the vinyl and thiol groups can undergo thiol-ene / yne click chemistry reactions to form a cross-linked network structure, thereby improving the elastic behavior of asphalt and partially replacing SBS.
[0007] In addition, during asphalt paving and in high temperature environments, asphalt easily volatilizes to produce asphalt fumes, which are mainly composed of sulfur dioxide and volatile organic compounds, and these asphalt fumes are extremely harmful to the human body.
[0008] Since the modified SBS is loaded with silver ions and titanium dioxide, the silver ions have a removal effect on benzene, the main component of volatile organic gases. When nano-titanium dioxide is exposed to light, it will excite its valence band electrons to cross the forbidden band into the conduction band, and at the same time form holes in the valence band. Since the holes have a significant ability to receive electrons, they can react with oxygen to produce OH - , thereby effectively eliminating sulfur dioxide.
[0009] Preferably, the photoinitiator is hydroxycyclohexyl phenyl ketone.
[0010] Preferably, the silver ions and titanium dioxide are added in the form of silver-loaded nano-titanium dioxide.
[0011] Preferably, the silver-loaded nano-titanium dioxide comprises the following raw materials in parts by weight: 800-1200 mg titanium dioxide, 20-40 mg silver nitrate and 0.4-0.6 g sodium borohydride.
[0012] Preferably, the preparation method of the silver-loaded titanium dioxide is: 800-1200 mg of titanium dioxide and 20-40 mg of silver nitrate are mixed in 500 ml of deionized water, and then 0.4-0.6 g of sodium borohydride is added for reduction reaction for 2-4 hours, and then filtered and washed, and vacuum dried at 60-80° C. to obtain silver-loaded titanium dioxide.
[0013] Compared with adding silver ions and titanium dioxide separately, adding silver ions and titanium dioxide in the form of silver-loaded nano-titanium dioxide can promote the synergistic gas elimination of silver ions and titanium dioxide, effectively improving its elimination effect on asphalt fume.
[0014] Preferably, the modified SBS is composed of SBS, trimethylolpropane triacrylate, trithiol [trimethylolpropane tris (3-mercaptopropionate)], octanediyne, surfactant B246, silver-loaded nano-titanium dioxide and deionized water.
[0015] Preferably, the modified SBS comprises the following raw materials in parts by mass: 30-40 parts of SBS, 2-4 parts of trimethylolpropane triacrylate, 1-3 parts of trimercapto [trimethylolpropane tris (3-mercaptopropionate)], 1-2 parts of octanediyne, 0.2-0.4 parts of surfactant B246, 8-10 parts of silver-loaded nano-titanium dioxide and 10-14 parts of deionized water.
[0016] Preferably, the preparation method of the modified SBS is: firstly, trimethylolpropane triacrylate, trithiol [trimethylolpropane tris (3-mercaptopropionate)], octanediyne and surfactant B246 are mixed, then deionized water is added dropwise, stirred again to form an emulsion, and finally SBS and silver-loaded nano-titanium dioxide are added to obtain the modified SBS.
[0017] The modified SBS uses trimethylolpropane triacrylate, trithiol [trimethylolpropane tris (3-mercaptopropionate)] and octanediyne as templates, and forms a complex cross-linked network through thiol-ene / yne click chemistry under the action of a photoinitiator. The addition of an aqueous phase causes a large number of micropores to exist in the cross-linked network, and these micropores will cause the cross-linked network structure to have a very strong adsorption capacity, thereby effectively adsorbing asphalt fumes, and further enhancing the degradation effect of asphalt fumes loaded with silver nano-titanium dioxide.
[0018] In a second aspect, the present application provides a method for preparing high-elasticity and high-viscosity asphalt, using the following technical solution: A method for preparing high-elastic and high-viscosity asphalt comprises the following steps: Step 1: Heat the base asphalt to 160-170°C, then add the modified SBS and mix and stir for 20-40 minutes, then increase the temperature to 165-175°C and shear for 60-80 minutes to obtain SBS modified asphalt; Step 2: Add a photoinitiator to the SBS modified asphalt, then heat to 170-190°C and shear for 80-100 minutes, and finally develop at 170-180°C for 30-40 minutes to obtain a high-elastic and high-viscosity asphalt.
[0019] In a third aspect, the present application provides an application of high-elasticity and high-viscosity asphalt, using the following technical solution: An application of high-elasticity and high-viscosity asphalt, wherein the high-elasticity and high-viscosity asphalt is applied to road construction, filling, 3D paving, and sand-containing fog sealing.
[0020] In summary, this application has the following beneficial effects: 1. Since the modified SBS contains a large amount of vinyl and thiol groups, under the catalytic action of the photoinitiator, the vinyl and thiol groups can undergo thiol-ene / yne click chemical reactions to form a cross-linked network structure, thereby improving the elastic behavior of asphalt and partially replacing SBS.
[0021] 2. During asphalt laying and in high temperature environments, asphalt is easy to volatilize and produce asphalt fumes, which are mainly composed of sulfur dioxide and volatile organic compounds. These asphalt fumes are extremely harmful to the human body; Since the modified SBS is loaded with silver ions and titanium dioxide, the silver ions have a removal effect on benzene, the main component of volatile organic gases. When nano-titanium dioxide is exposed to light, it will excite its valence band electrons to cross the forbidden band into the conduction band, and at the same time form holes in the valence band. Since the holes have a significant ability to receive electrons, they can react with oxygen to produce OH - , thereby effectively eliminating sulfur dioxide.
[0022] 3. Compared with adding silver ions and titanium dioxide separately, adding silver ions and titanium dioxide in the form of silver-loaded nano-titanium dioxide can promote the synergistic gas elimination of silver ions and titanium dioxide, effectively improving its elimination effect on asphalt fume.
[0023] 4. The modified SBS uses trimethylolpropane triacrylate, trithiol [trimethylolpropane tris (3-mercaptopropionate)] and octanediyne as templates, and forms a complex cross-linked network through thiol-ene / yne click chemistry under the action of photoinitiator. The addition of water phase causes a large number of micropores in the cross-linked network, and these micropores will cause the cross-linked network structure to have a strong adsorption capacity, thereby effectively adsorbing asphalt fume, and further improving the degradation effect of asphalt fume loaded with silver nano-titanium dioxide. DETAILED DESCRIPTION
[0024] The present application is further described in detail below in conjunction with Examples 1-7 and Comparative Example 1.
[0025] raw material: Base asphalt SK-90 # ; SBS Sinopec YH-1401; Hydroxycyclohexyl phenyl ketone CAS: 947-19-3; Titanium dioxide CAS: 1317-80-2; Silver nitrate CAS: 7761-88-8; Sodium borohydride CAS: 16940-66-2; Trimethylolpropane triacrylate CAS: 15625-89-5; Trimercapto [trimethylolpropane tris (3-mercaptopropionate)] CAS: 33007-83-9; Octadiyne CAS: 871-84-1; Surfactant B246 Croda.
[0026] Example Example 1 A high-elastic and high-viscosity asphalt comprises the following raw materials: 100 kg of base asphalt, 16 kg of modified SBS and 1.5 kg of photoinitiator-hydroxycyclohexyl phenyl ketone.
[0027] A method for preparing high-elastic and high-viscosity asphalt comprises the following steps: Step 1: Heat the base asphalt to 160°C, then add the modified SBS and mix and stir for 30 minutes, then increase the temperature to 175°C and shear for 70 minutes to obtain SBS modified asphalt; Step 2: Add a photoinitiator to the SBS modified asphalt, then heat to 180°C and shear for 90 minutes, and finally develop at 175°C for 35 minutes to obtain a high-elastic and high-viscosity asphalt.
[0028] The modified SBS includes the following raw materials: 35 kg SBS, 3 kg trimethylolpropane triacrylate, 2 kg trimercapto [trimethylolpropane tris (3-mercaptopropionate)], 1.5 kg octanediyne, 0.3 kg surfactant B246, 9 kg silver-loaded nano-titanium dioxide and 12 kg deionized water.
[0029] The preparation method of modified SBS is as follows: firstly, trimethylolpropane triacrylate, trithiol [trimethylolpropane tris (3-mercaptopropionate)], octanediyne and surfactant B246 are mixed, then deionized water is added dropwise, stirred again to form an emulsion, and finally SBS and silver-loaded nano-titanium dioxide are added to obtain modified SBS.
[0030] The silver-loaded nano-titanium dioxide comprises the following raw materials: 1000 mg titanium dioxide, 30 mg silver nitrate and 0.5 g sodium borohydride.
[0031] The preparation method of silver-loaded titanium dioxide is as follows: 1000 mg of titanium dioxide and 30 mg of silver nitrate were mixed in 500 ml of deionized water, and then 0.5 g of sodium borohydride was added for reduction reaction for 3 hours, and then filtered, washed, and vacuum dried at 70° C. to obtain silver-loaded titanium dioxide.
[0032] Example 2-3 The difference from Example 1 is that the added amounts of titanium dioxide and silver nitrate are different, as shown in Table 1.
[0033] Table 1 Addition amount of each component of silver-loaded nano-titanium dioxide in Examples 1-3 / mg
[0034] Example 4 A high-elastic and high-viscosity asphalt comprises the following raw materials: 100kg of base asphalt, 16kg of SBS-silver-loaded nano-titanium dioxide mixture and 1.5kg of photoinitiator-hydroxycyclohexyl phenyl ketone; wherein the mass ratio of SBS to silver-loaded nano-titanium dioxide is 35:9.
[0035] A method for preparing high-elastic and high-viscosity asphalt comprises the following steps: Step 1: Heat the base asphalt to 160°C, then add the SBS-silver-loaded nano-titanium dioxide mixture and mix and stir for 30 minutes, then increase the temperature to 175°C and shear for 70 minutes to obtain SBS modified asphalt; Step 2: Add a photoinitiator to the SBS modified asphalt, then heat to 180°C and shear for 90 minutes, and finally develop at 175°C for 35 minutes to obtain a high-elastic and high-viscosity asphalt.
[0036] The silver-loaded nano-titanium dioxide comprises the following raw materials: 1000 mg titanium dioxide, 30 mg silver nitrate and 0.5 g sodium borohydride.
[0037] The preparation method of silver-loaded titanium dioxide is as follows: 1000 mg of titanium dioxide and 30 mg of silver nitrate were mixed in 500 ml of deionized water, and then 0.5 g of sodium borohydride was added for reduction reaction for 3 hours, and then filtered, washed, and vacuum dried at 70° C. to obtain silver-loaded titanium dioxide.
[0038] Example 5 A high-elastic and high-viscosity asphalt comprises the following raw materials: 100 kg of base asphalt, 16 kg of modified SBS and 1.5 kg of photoinitiator-hydroxycyclohexyl phenyl ketone.
[0039] A method for preparing high-elastic and high-viscosity asphalt comprises the following steps: Step 1: Heat the base asphalt to 160°C, then add the modified SBS and mix and stir for 30 minutes, then increase the temperature to 175°C and shear for 70 minutes to obtain SBS modified asphalt; Step 2: Add a photoinitiator to the SBS modified asphalt, then heat to 180°C and shear for 90 minutes, and finally develop at 175°C for 35 minutes to obtain a high-elastic and high-viscosity asphalt.
[0040] The modified SBS includes the following raw materials: 35 kg SBS, 3 kg trimethylolpropane triacrylate, 2 kg trimercapto [trimethylolpropane tris (3-mercaptopropionate)], 1.5 kg octanediyne, 0.3 kg surfactant B246, 9 kg silver-loaded nano-titanium dioxide and 12 kg deionized water.
[0041] The preparation method of modified SBS is as follows: firstly, trimethylolpropane triacrylate, trithiol [trimethylolpropane tris (3-mercaptopropionate)], octanediyne and surfactant B246 are mixed, then deionized water is added dropwise, stirred again to form an emulsion, and finally SBS and silver-loaded nano-titanium dioxide are added to obtain modified SBS.
[0042] Silver-loaded nano-titanium dioxide is prepared by mixing 1000 mg of titanium dioxide and 30 mg of silver nitrate.
[0043] Embodiment 6-7 The difference from Example 1 is that the addition amount of each component of the modified SBS is different, as shown in Table 2.
[0044] Table 2 Addition amount of each component of modified SBS in Example 1 and Examples 6-7 / kg
[0045] Comparative Example Comparative Example 1 A high-elastic and high-viscosity asphalt comprises the following raw materials: 100kg of base asphalt, 16kg of SBS and 1.5kg of photoinitiator-hydroxycyclohexyl phenyl ketone.
[0046] A method for preparing high-elastic and high-viscosity asphalt comprises the following steps: Step 1: Heat the base asphalt to 160°C, then add SBS and mix and stir for 30 minutes, then increase the temperature to 175°C and shear for 70 minutes to obtain SBS modified asphalt; Step 2: Add a photoinitiator to the SBS modified asphalt, then heat to 180°C and shear for 90 minutes, and finally develop at 175°C for 35 minutes to obtain a high-elastic and high-viscosity asphalt.
[0047] Performance testing Detection Methods 1. Viscosity elasticity test Three samples were taken from Example 1, Examples 6-7 and Comparative Example 1, respectively, and then the samples were subjected to 60°C viscosity test and elastic recovery test according to JTG E20-2011 "Test Procedure for Asphalt and Asphalt Mixtures for Highway Engineering". The test results were averaged, and the test data are shown in Table 3.
[0048] Table 3 Viscosity elasticity test table of Example 1, Examples 6-7 and Comparative Example 1
[0049] 2. Asphalt smoke suppression effect test Three 20kg samples were taken from Examples 1-5 and Comparative Example 1 respectively, and the asphalt fume released during sample preparation was collected through glass filter paper. The glass filter paper was then dried to evaporate all the water on the glass filter paper. The weight difference before and after the glass filter paper was calculated and the average value was taken to obtain the asphalt fume generation amount.
[0050] The test results are shown in Table 4.
[0051] Table 4 Asphalt smoke suppression effect table of Examples 1-5 and Comparative Example 1
[0052] With reference to Example 1 and Comparative Example 1 and in combination with Tables 3-4, it can be seen that, relative to Comparative Example 1, the 60°C viscosity (vacuum decompression capillary) Pa·s and elastic recovery of Example 1 are significantly improved, and the amount of asphalt fume generated is also significantly reduced. This shows that, relative to the use of conventional SBS, the use of modified SBS can effectively improve the elasticity and viscosity of high-elastic and high-viscosity asphalt, that is, the amount of SBS added is reduced under the same parameters, and the modified SBS can effectively suppress asphalt fume.
[0053] The reason is that since the modified SBS contains a large amount of vinyl and thiol groups at the same time, under the catalysis of the photoinitiator, the vinyl and thiol groups can undergo thiol-ene / yne click chemistry reactions to form a cross-linked network structure, thereby improving the elastic behavior of asphalt and partially replacing SBS.
[0054] With reference to Examples 1-3 and in combination with Table 4, it can be seen that, relative to Example 1, the asphalt fume generation of Examples 2-3 is significantly increased. This indicates that when titanium dioxide and silver nitrate are added in the amounts of Example 1, the prepared high-elastic and high-viscosity asphalt will have a better asphalt fume suppression effect.
[0055] Referring to Example 1 and Example 4 and combining with Table 4, it can be seen that compared with Example 1, the asphalt fume of Example 4 is significantly improved, which shows that the presence of the vinyl-thiol system in the modified SBS can effectively inhibit the generation of asphalt fume.
[0056] The reason is that trimethylolpropane triacrylate, trithio [trimethylolpropane tris (3-mercaptopropionate)] and octanediyne are used as templates to form a complex cross-linked network through thiol-ene / yne click chemistry under the action of photoinitiator, and the addition of water phase leads to the presence of a large number of micropores in the cross-linked network, and these micropores will enable the cross-linked network structure to have a very strong adsorption capacity, thereby effectively adsorbing asphalt fume, and further improving the degradation effect of asphalt fume loaded with silver nano-titanium dioxide.
[0057] At the same time, compared with the comparative example 1, the asphalt fume of the embodiment 4 is significantly lower, which shows that the silver ions and nano-titanium dioxide have a very good asphalt fume treatment effect.
[0058] The reason is that asphalt fume is mainly composed of sulfur dioxide and volatile organic compounds, which are extremely harmful to the human body. Silver ions have a removal effect on benzene, the main component of volatile organic gas. When exposed to light, nano-titanium dioxide will excite its valence band electrons to cross the forbidden band into the conduction band, and at the same time form holes in the valence band. Since the holes have significant electron-accepting ability, they can react with oxygen to produce OH -, thereby effectively eliminating sulfur dioxide.
[0059] With reference to Example 1 and Example 5 and in combination with Table 4, it can be seen that, relative to Example 1, the amount of asphalt fume generated in Example 5 is significantly increased. This indicates that, relative to the use of nano-titanium dioxide and silver nitrate alone, adding silver ions and titanium dioxide in the form of silver-loaded nano-titanium dioxide can further enhance the treatment effect of high-elastic and high-viscosity asphalt on asphalt fume.
[0060] The reason is that adding silver ions and titanium dioxide in the form of silver-loaded nano-titanium dioxide can promote the synergistic gas elimination of silver ions and titanium dioxide, effectively improving its elimination effect on asphalt fume.
[0061] With reference to Example 1 and Examples 6-7 and in combination with Table 3, it can be seen that, relative to Example 1, the 60°C viscosity (vacuum decompression capillary) Pa·s and elastic recovery of Examples 6-7 are slightly decreased, which indicates that when the components of the modified SBS are formulated in the same proportion as in Example 1, the prepared high-elastic and high-viscosity asphalt will have better elasticity, viscosity and asphalt fume suppression effect.
[0062] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-elastic and high-viscosity asphalt, characterized in that: The invention comprises the following raw materials in parts by weight: 90-110 parts of base asphalt, 12-18 parts of modified SBS and 1-2 parts of photoinitiator, wherein the modified SBS contains vinyl and mercapto, and the modified SBS is loaded with silver ions and titanium dioxide.
2. The high-elasticity and high-viscosity asphalt according to claim 1 is characterized by: The silver ions and titanium dioxide are added in the form of silver-loaded nano-titanium dioxide.
3. The high-elasticity and high-viscosity asphalt according to claim 2 is characterized in that: The silver-loaded nano-titanium dioxide comprises the following raw materials in parts by weight: 800-1200 mg of titanium dioxide, 20-40 mg of silver nitrate and 0.4-0.6 g of sodium borohydride.
4. The high-elastic and high-viscosity asphalt according to claim 3 is characterized in that: The preparation method of the silver-loaded titanium dioxide is: 800-1200 mg of titanium dioxide and 20-40 mg of silver nitrate are mixed in 500 ml of deionized water, and then 0.4-0.6 g of sodium borohydride is added for reduction reaction for 2-4 hours, and then filtered and washed, and vacuum dried at 60-80° C. to obtain silver-loaded titanium dioxide.
5. The high-elasticity and high-viscosity asphalt according to claim 1 is characterized by: The modified SBS is composed of SBS, trimethylolpropane triacrylate, trithiol [trimethylolpropane tris (3-mercaptopropionate)], octanediyne, surfactant B246, silver-loaded nano-titanium dioxide and deionized water.
6. The high-elasticity and high-viscosity asphalt according to claim 5, characterized in that: The modified SBS comprises the following raw materials in parts by weight: 30-40 parts of SBS, 2-4 parts of trimethylolpropane triacrylate, 1-3 parts of trithiol [trimethylolpropane tris (3-mercaptopropionate)], 1-2 parts of octadiyne, 0.2-0.4 parts of surfactant B246, 8-10 parts of silver-loaded nano-titanium dioxide and 10-14 parts of deionized water.
7. The high-elasticity and high-viscosity asphalt according to claim 5, characterized in that: The preparation method of the modified SBS is: First, trimethylolpropane triacrylate, trithiol [trimethylolpropane tris (3-mercaptopropionate)], octanediyne and surfactant B246 are mixed, and then deionized water is added dropwise, and stirred again to form an emulsion, and finally SBS and silver-loaded nano-titanium dioxide are added to obtain modified SBS.
8. A method for preparing the high-elastic and high-viscosity asphalt according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: Heat the base asphalt to 160-170°C, then add the modified SBS and mix and stir for 20-40 minutes, then increase the temperature to 165-175°C and shear for 60-80 minutes to obtain SBS modified asphalt; Step 2: Add a photoinitiator to the SBS modified asphalt, then heat to 170-190°C and shear for 80-100 minutes, and finally develop at 170-180°C for 30-40 minutes to obtain a high-elastic and high-viscosity asphalt.
9. An application of the high-elasticity and high-viscosity asphalt according to any one of claims 1 to 7, characterized in that: The high-elasticity and high-viscosity asphalt is used in road construction, filling, 3D paving, and sand-containing fog sealing.
